FINANCIAL STRATEGIES TO INCREASE BUSINESS SUSTAINABILITY - Adi Mursalin; Naiyun Untung Utama; Antoni (CV. Adiba Aisha Amira, 2025)
A good business financial strategy is one of the main keys to developing a business to be bigger and more sustainable. A successful business not only depends on quality products or services, but also requires efficient and strategic financial management. When business finances are well managed, companies can allocate funds wisely, avoid excessive debt, increase liquidity, and make sound business decisions. By implementing appropriate financial management strategies, businesses can improve their performance, maintain financial stability, and ensure long-term sustainability. That's why understanding and applying these principles is so important to business success. The method used in this article is a literature review. Literature studies can be obtained from various sources, including journals, books, the internet and libraries. This research discusses the definition of business sustainability, the role of financial strategy in business sustainability, and the success of financial strategy in increasing business sustainability.